TINGKAT PENGETAHUAN ANATOMI FISIOLOGI PADA PROGRAM STUDI KEPERAWATAN DAN KEBIDANAN DI STIKES HARAPAN BANGSA PURWOKERTO - Rahmaya Nova Handayani (Universitas Harapan Bangsa Purwokerto, 2017)
Anatomy and physiology courses are basic courses that are critical to student health, especially nursing and midwifery. This subject is considered difficult by most students. Lecture method applied during the lectures less varied. The learning method used is still perceived less support student success in achieving adequate competence. The purpose of this study is the difference in the level of students' knowledge Knowing Prodi D3 in Midwifery, Nursing D3 and S1 Nursing and influencing factors in STIKES Harapan BangsaPurwokerto. This design of this study is to use quantitative descriptive overview of variebel be studied. This study analyzed the differences in knowledge of anatomy physiology courses in Midwifery D3 and S1 Nursing Nursing and the factors that influence it. The samples used was 60 taken on the respondent 4th semester program of study midwifery and nursing D3 S1. The analysis is using univariate frequency distribution. The results of this study is the average value of the respondents Nursing study program S1 is 33.4 while the D3 Midwifery study program is 29 to knowledge of respondents on both courses in the low category. Keywords: Anatomy Physiology, knowledge, midwifery and nursing students